Creating a Renaissance for the Library in the Digital Era - Cousins, Jill (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
This paper provides a history of European Union Digital Library programmes from the 1990’s to 2015 and illustrates the key role played by Pat Manson. A series of major initiatives such as GABRIEL, TEL and DELOS as well as the Europeana Project are fully described. The paper focuses on policy issues and also explores how thinking was translated into other cultural heritage sectors.